Intuitive versus theory-based assessment of consciousness: The problem of low-level consciousness - Kotchoubey, Boris; Lang, Simone (Clinical neurophysiology, 2011)
Functional connectivity (fcMRI) analyses of resting state functional magnetic resonance imaging (fMRI) data revealed substantial differences between states of consciousness. The underlying cause-effect linkage, however, remains unknown to the present day. The aim of this study was to examine the relationship between fcMRI measures and Disorders of Consciousness (DOC) in resting state and under adequate stimulation. - fMRI data from thirteen patients with unresponsive wakefulness syndrome, eight patients in minimally conscious state, and eleven healthy controls were acquired in rest and during the application of nociceptive and emotional acoustic stimuli. We compared spatial characteristics and anatomical topography of seed-based fcMRI networks on group and individual levels. - The anatomical topography of fcMRI networks of patients was altered in all three conditions as compared with healthy controls. Spread and distribution of individual fcMRI networks, however, differed significantly between patients and healthy controls in stimulation conditions only. The exploration of individual metric values identified two patients whose spatial metrics did not deviate from metric distributions of healthy controls in a statistically meaningful manner. - These findings suggest that the disturbance of consciousness in DOC is related to deficits in global topographical network organization rather than a principal inability to establish long-distance connections. In addition, the results question the claim that task-free measurements are particularly valuable as a tool for individual diagnostics in severe neurological disorders. Further studies comparing connectivity indices with outcome of DOC patients are needed to determine the clinical relevance of spatial metrics and stimulation paradigms for individual diagnosis, prognosis and treatment in DOC. - Evaluation of a short two-tone oddball paradigm to discriminate between the vegetative state (VS) and minimal consciousness state (MCS) in a sample of patients with severe disorders of consciousness (DOC). - EEG was recorded from 45 DOC patients and 14 healthy participants while listening to an auditory oddball paradigm presented in a passive - just listen - and an active - count the odd tones - condition. In patients, the experiment was repeated after a minimum of one week. - Prevalence of the P300 was higher in healthy participants (71%) than in patients, but did not discriminate between VS (T1: ∼10%; T2: ∼11%) and MCS (T1: ∼13%; T2: 25%) patients. - Results cast doubt on whether this simple auditory stimulation paradigm, which requires cognitive action from the listener, is sensitive enough to discriminate between patients with DOC. - The sensitivity of the P300 ERP obtained in a short two-tone oddball paradigm presented in a passive and an active condition appears to be too low for routine application in a clinical setting aiming at distinguishing between VS and MCS patients. - The value of resting electroencephalogram (EEG) in revealing neural constitutes of consciousness (NCC) was examined. We quantified the dynamic repertoire, duration and oscillatory type of EEG microstates in eyes-closed rest in relation to the degree of expression of clinical self-consciousness. For NCC a model was suggested that contrasted normal, severely disturbed state of consciousness and state without consciousness. Patients with disorders of consciousness were used. Results suggested that the repertoire, duration and oscillatory type of EEG microstates in resting condition quantitatively related to the level of consciousness expression in brain-damaged patients and healthy-conscious subjects. Specifically, results demonstrated that (a) decreased number of EEG microstate types was associated with altered states of consciousness, (b) unawareness was associated with the lack of diversity in EEG alpha-rhythmic microstates, and (c) the probability for the occurrence and duration of delta-, theta- and slow-alpha-rhythmic microstates were associated with unawareness, whereas the probability for the occurrence and duration of fast-alpha-rhythmic microstates were associated with consciousness. In conclusion, resting EEG has a potential value in revealing NCC. This work may have implications for clinical care and medical-legal decisions in patients with disorders of consciousness.
Gesehen am 07.07.2022